Nectar‐Feeding Behavior in the Mallee Ringneck, Barnardius zonarius barnardi - Amanda E. Hewes; Alejandro Rico‐Guevara; Todd J. McWhorter (Ecology and Evolution)
ABSTRACT Opportunistic nectarivory occurs in many avian lineages around the world. In order to understand the implications of this behavior to plant reproduction via pollination and to other nectarivores via competition, more thorough descriptions of opportunistic nectar‐feeding behavior are necessary. We observed nectar feeding of the mallee ringneck, Barnardius zonarius barnardi, on flowers of the spotted emu bush, Eremophila maculata, in the temperate mallee of South Australia. Here, we describe the nectar‐feeding behavior of B. zonarius barnardi and discuss the implications for competition with honeyeaters and the reproduction of E. maculata. We also compare the morphology of the feeding apparatus of B. zonarius barnardi with that of nectarivorous parrots, lorikeets and lories, to determine whether they share convergent morphological features to facilitate the consumption of nectar. Finally, we suggest avenues for future natural history work to better document opportunistic avian nectarivory in Australian ecosystems.